Tasawuf dalam Perspektif Sayyed Hossein Nasr - Lukman Lukman (IAIN Bengkulu, 2019)
This paper aims to see the modern human side is experiencing various acute crises, which originated from the spiritual crisis that befell them, as a result of the development of western technology that is not aligned with esoteric values. The science and technology that has been worshiped thus becomes a trigger for humans by flowing the increasingly powerful flow of globalization and information, science eventually becomes the ruler and dominates nature. On the other hand there are some groups of the world community there are also those who have started to get bored even disgusted with the life of glamoristic, materialistic, hedonistic, unhealthy competition, greed, arrogance, sadism, violence and so on. The method used in this paper is to analyze Sayyed Hosein Nasr's thoughts with a qualitative-descriptive approach. The results obtained from this release are Sufism is the right way to answer the various problems faced by the modern world. Sufism that does not leave material physical life. The meaning of uzlah (self-exile), hold hermitage) and khalwah (solitude) is interpreted in spirit or soul, not in physical material. The theme of exile arises from within the souls of modern humans to remind them of the deepest spiritual needs. Therefore sufism is the right way to fill the emptiness of the human soul as a result which leads to western oriented and material oriented.